Modified Protocol Decreases Surgical Site Infections after Total Knee Arthroplasty - Lamplot, Joseph D.; Luther, Gaurav; Mawdsley, Emily Landon; Luu, Hue H.; Manning, David (The Journal of Knee Surgery, 2015)
We investigate the effectiveness of a comprehensive aseptic protocol in reducing surgical site infection (SSI) after knee arthroplasty in a single medical center with a high prevalence of MRSA. A database of all patients in a single center undergoing primary knee arthroplasty between 2005 and 2011 was reviewed for SSI using Centers for Disease Control criteria and AAOS guidelines. All patients were treated with an aseptic protocol consisting of the following: preoperative 2% mupirocin nasal ointment and 0.4% chlorhexidine surgical site wipes, modified instrument care, perioperative prophylactic vancomycin and cefazolin, and surgical site skin preparation with chlorhexidine, alcohol, and iodophor. We compare our protocol total knee arthroplasty SSI rate to our institutional historical control (2001–2004) and to contemporary literature. Among 1,224 patients, 70% were ASA class >2 and 64% had a body mass index (BMI) > 30 kg/m2. We found an overall 0.49% infection rate, significantly lower than that of our institutional historical control (0.49 vs. 2.24%, p < 0.001; odds ratio [OR], 0.21; number needed to treat [NNT], 145) and seven recently published reports (p < 0.001–0.042; OR, 0.07–0.42). Compared with these reports, significantly more of our patients were ASA class > 2, BMI > 30 kg/m2, immunosuppressed, or had rheumatoid arthritis. Our aseptic protocol decreases SSI in a high-risk population undergoing knee arthroplasty in a medical center and community with a high prevalence of MRSA.
Keywords: surgical site infection; aseptic protocol; total knee arthroplasty; antibiotic prophylaxis